Thermal degradation behavior of the compound containing phosphaphenanthrene and phosphazene groups and its flame retardant mechanism on epoxy resin - Qian, Lijun; Ye, Longjian; Qiu, Yong; Qu, Shuren (Polymer (Guilford), 2011)
The flame retardant epoxy resin has been prepared by mixing the flame retardant additive hexa-(phosphaphenanthrene-hydroxyl-methyl-phenoxyl)-cyclotriphosphazene (HAP-DOPO) into diglycidyl ether of bisphenol-A (DGEBA). After cured by 4,4′-Diamino-diphenyl sulfone (DDS), the flame retardant properties of thermosets were characterized by the limited oxygen index (LOI), UL-94 test and cone calorimeter. The results show the lower peak of heat release rate (pk-HRR), the higher flammability rating than that of flame retardant epoxy resin by 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), hexa-phenoxyl-cyclotriphosphazene (HPCP) and their mixture cloning the ratio of group component of HAP-DOPO. The degradation route of HAP-DOPO was disclosed by thermogravimetric analysis (TGA), the real time Fourier transform infrared spectra (FTIR), thermogravimetric analysis/infrared spectrometry (TGA-FTIR), pyrolysis gas chromatography mass/spectrometry (Py-GC/MS). During combustion, HAP-DOPO continues to release the PO radicals and o-phenylphenoxyl radical during two degradation stages from 200 °C for its unstable trisubstituted methyl structure of HAP-DOPO, inhibits the chain reaction of decomposition and exerts the flame retardant effect in gas phase. The phosphazene groups link with the residual phosphate from degraded phosphaphenanthrene, which increases the crosslink density of residue, effectively promotes the formation of high-strength, high-yield and phosphorus-rich char layer. The structure of HAP-DOPO shows a remarkable flame retardant molecular structure-effect on enhancing the flame retardant efficiency on thermosets. [Display omitted]